2017
DOI: 10.18632/oncotarget.17055
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-related protein 2 induces G0/G1 arrest and apoptosis through suppressing Wnt/β-catenin signaling and is frequently methylated in breast cancer

Abstract: Dickkopf-related protein 2 (DKK2) is one of the antagonists of Wnt/β-catenin signaling, with its downregulation reported in multiple cancers. However, how DKK2 contributes to breast tumorigenesis remains unclear. We examined its expression and promoter methylation in 10 breast tumor cell lines, 98 primary tumors, and 21 normal breast tissues. Compared with normal tissues, DKK2 was frequently silenced in breast cell lines (7/8). DKK2 promoter methylation was detected in 77.8% of cell lines and 86.7% of breast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
(56 reference statements)
3
17
0
Order By: Relevance
“…On the whole, we comprehensively analyzed the expression profiles and prognostic value of DKKs in breast cancer subtypes. The main data indicated that a high DKK2 mRNA expression was associated with a better prognosis in breast cancer, which is consistent with the findings of a previous study ( 28 ). Nevertheless, we focused our attention on the clinical prognostic value of DKK2 in the normal-like subtype.…”
Section: Resultssupporting
confidence: 92%
“…On the whole, we comprehensively analyzed the expression profiles and prognostic value of DKKs in breast cancer subtypes. The main data indicated that a high DKK2 mRNA expression was associated with a better prognosis in breast cancer, which is consistent with the findings of a previous study ( 28 ). Nevertheless, we focused our attention on the clinical prognostic value of DKK2 in the normal-like subtype.…”
Section: Resultssupporting
confidence: 92%
“…Our results for patients after a primary resection are consistent with previous studies for gastric, colon, breast and hepatocellular carcinoma, where DKK2 was found as a tumor suppressor and its loss is associated with activation of the Wnt-pathway and consecutive tumor progression [19][20][21][22][23][24].…”
Section: Dkk2 Expression and Its Impact On Survivalsupporting
confidence: 91%
“…Dickkopf-related protein 2 induces G0/G1 arrest and cell apoptosis by suppressing β-catenin activity in breast CSCs. 163 DACT1, a homolog of Dapper that is located at chromosomal region 14q23.1, promotes apoptosis in breast CSCs by antagonizing the Wnt/β-catenin signaling pathway. 164 Cadherin-11, a proapoptotic tumor suppressor, reduces the level of active phospho-β-catenin (ser552) to induce apoptosis in colorectal CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%